Dopamine agonists for restless legs syndrome - Pran Phakdeekitcharoen; Michael J Keogh (Advances in Clinical Neuroscience & Rehabilitation)
Restless Legs Syndrome (RLS) is a common neurological disorder characterised by an uncontrollable urge to move the legs. Dopamine agonists are widely used as first or second-line treatments for RLS due to their efficiency in alleviating the symptoms of RLS and improving sleep quality. Whilst efficacious, dopamine agonists can also cause several side effects which are important to understand and monitor. This article aims to provide a practical overview of when and how to prescribe dopamine agonists together with appropriate monitoring advice for clinicians.